2015
DOI: 10.2298/gensr1502559a
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heritability of selected rice varieties for grain yield, its components and grain quality characters

Abstract: This study was conducted to determine the combining ability and heritability of rice grain yield, its components and some grain quality traits such as amylose content (AC), gelatinization temperature (GT), gel consistency (GC) and head rice recovery (HRR). The study was commenced by crossing the selected rice varieties based on a full diallel mating design. The F1 was harvested at the end of the season. In the following season, the crossed, reciprocal and parental lines were planted in random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Estimation of narrow sense heritability showed that the FGN, PN, PL and GC had the lowest values while the other traits had either moderate or high heritability, which indicated selection in the early generations could be done to fix the favorable genes (Table 6). ALLAHGHOLIPOUR et al (2015) reported that narrow sense heritability for GY and GC had the lowest values and it was high for AC and moderate for GC and PN. MOELJOPAWIRO (2015) reported high heritability estimates in the broad sense and Moderate narrow sense heritability estimates for PL and HGW, suggested that these traits can be selected with the pedigree method.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of narrow sense heritability showed that the FGN, PN, PL and GC had the lowest values while the other traits had either moderate or high heritability, which indicated selection in the early generations could be done to fix the favorable genes (Table 6). ALLAHGHOLIPOUR et al (2015) reported that narrow sense heritability for GY and GC had the lowest values and it was high for AC and moderate for GC and PN. MOELJOPAWIRO (2015) reported high heritability estimates in the broad sense and Moderate narrow sense heritability estimates for PL and HGW, suggested that these traits can be selected with the pedigree method.…”
Section: Discussionmentioning
confidence: 99%
“…9 parents and 36 crosses over the three seasons (Table 2). Significant variation for the yield traits in rice were reported by Hosseini et al (2005), Sharma (2006), Dey et al (2013) and Allahgholipour et al (2015).…”
mentioning
confidence: 90%